UPAYA PENINGKATAN PEMAHAMAN PECEGAHAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN SD NEGERI 2 SUMUR MELALUI TIM PENCEGAHAN DAN PENANGANAN KEKERASAN (TPPK) - Bayu Septian Anuraga; Arri Handayami; Dini Rakhmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study is to inform school principals, educators, learners, parents and communities about the importance of protecting children from violence that occurs within the education unit and in activities outside the school environment. This research uses a descriptive qualitative approach because it applies non-statistical analysis and considers the opinions of others. The research used data reduction techniques, data presentation and conclusion drawing, conducted at school institutions. The results of this study is sexual violence is violence committed by someone by forcing the victim to engage in sexual activity. Sexual violence often has a traumatic impact on children and adults. However, cases of sexual violence often go unreported because people deny that it happens. Many cases of sexual violence are happening around us and need to be addressed. With the cases of sexual violence against children, it is necessary to have a TPPK team that will be implemented at SD Negeri 2 Sumur to anticipate the occurrence of sexual violence in this school.